Islamic Education in Europe, The Middle East, and Asia: Historical and Contemporary Perspectives - Firdaus, Nazilatul Fatihah; Kurjum, Mohammad (Kuttab: Jurnal Ilmu Pendidikan Islam, 2026)
This study examines Islamic education in Europe, the Middle East, and Asia from historical and contemporary perspectives. Using library research with a qualitative descriptive-comparative approach, data were collected from academic journals, books, and policy documents published between 2020 and 2024. Content analysis and cross-regional comparison were employed to identify educational orientation, curriculum structure, sociopolitical context, and contemporary challenges. The findings show that Islamic education is dynamic and adaptive, shaped by diverse historical and sociocultural contexts. In Europe, Islamic education has shifted from the intellectual legacy of Andalusia to a minority-based system emphasizing identity and social integration. In the Middle East, it balances classical traditions with modern reforms amid ideological and political dynamics. In Asia, Islamic education demonstrates contextual adaptation through integration with local culture, national education systems, and digital technology. Major challenges include digital transformation, educational inequality, ideological tensions, and curriculum reform.